Tabuik dalam Pembelajaran Bangun Ruang dengan Pendidikan matematika Realistik (PMR) - Fitriza, Rozi; Gunawan, Indra (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Learning and teaching will be meaningful if the students take an active role in finding the concept. The involvement of various contexts that are close to and known by students in learning and teaching mathematics motivate their learning and students see the importance of learning math. The use of cultural object such as tabuik in learning mathematics with Realistic Mathematics Education (RME) approach becomes an innovative learning at grade VIII of SMPN 4 Pariaman. Learning of polyhedrons (prism and pyramid) topic appropriate with the tabuik, which is built from several polyhedrons. This experimental study aims to see the comparison of student learning outcomes taught by RME approach using tabuik with student learning outcomes taught by conventional learning. The result of data analysis showed that the result of mathematics learning outcomes of students taught by Approach of Realistic Mathematics Education (RME) using tabuik in learning of polyhedron topic higher than mathematics learning outcomes of students taught by conventional learning at grade VIII SMPN 4 Pariaman. In addition, learning with RME approach and tabuik foster positive students' activities and positive attitudes in mathematics learning also appreciate their own culture.Keywords: Realistic Mathematics Education (RME), tabuik, learning outcomes.